Stay : a history of suicide and the philosophies against it - Hecht, Jennifer Michael, 1965- (Yale University Press, 2013)
Worldwide, more people die by suicide than by murder, and many more are left behind to grieve. Despite distressing statistics that show suicide rates rising, the subject, long a taboo, is infrequently talked about. In this sweeping intellectual and cultural history, poet and historian Jennifer Michael Hecht channels her grief for two friends lost to suicide into a search for history's most persuasive arguments against the irretrievable act, arguments she hopes to bring back into public consciousness. From the Stoics and the Bible to Dante, Shakespeare, Wittgenstein, and such twentieth-century writers as John Berryman, Hecht recasts the narrative of our "secular age" in new terms. She shows how religious prohibitions against self-killing were replaced by the Enlightenment's insistence on the rights of the individual, even when those rights had troubling applications. This transition, she movingly argues, resulted in a profound cultural and moral loss: the loss of shared, secular, logical arguments against suicide. By examining how people in other times have found powerful reasons to stay alive when suicide seems a tempting choice, she makes a persuasive intellectual and moral case against suicide